How foreign-born workers foster exports - Léa Marchal; Clément Nedoncelle (Kiel Institute for the World Economy (IfW), 2017)
We investigate the export-enhancing effect of foreign workers at the firm level. We first develop a theoretical framework of heterogeneous firms, assuming that foreign workers allow for productivity gains and convey valuable information on foreign markets. We illustrate that foreign workers foster exports at the extensive and the intensive margins. This effect can be decomposed in a general effect - to which any foreign worker contributes - and a destination-specific effect - to which only foreign workers who were born in the export destination contribute. We test these theoretical predictions using French firm-level data over the 1997-2008 period and a propensity score matching method to address endogeneity concerns. We find that foreign-born workers, and especially skilled individuals, foster exports at both margins. On average, a firm employing foreign-born workers exports 30% more in value than a control firm. We find evidence that this increase is spread over all destinations, suggesting that the effect of foreign-born workers goes beyond a destination-specific informational channel.
Keywords: F14; F22; F16; 330; Foreign-born workers; Exports; Firms; Heterogeneity; Productivity